Pengaruh Konseling Kelompok Art Therapy Untuk Meningkatkan Self Esteem Bagi Mahasiswa - Sinthia, Rita; Afriwilda, Mayang T; Saputra, Adif Jawadi; Qonaah, Liza (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2025)
This study aims to see the effect of group counseling with Art therapy techniques toincrease self esteem for students who experience comunication aprehension. The researchsubjects were 1st semester Guidance and Counseling Study Program students usingpurposive sampling. The action research method was used in this study. The number ofresearch subjects was 7 first semester students of the Guidance and Counseling studyprogram. Data collection techniques in this research (1) in the form of self-esteemquestionnaire developed measuring aspects of significance, competence, power, andvirtue, (2) communication apprehension questionnaire and (3) treatment through groupcounseling. The results showed the effect of art therapy group counseling to increase selfesteem for students who experience communication apprehension.